WASTE TREATMENT IN TEXTILE INDUSTRY IN SAN JUAN DE LURIGANCHO - Morán Paredes, Gladys Ivonne (2020)
Objective: To determine the characteristics in relation to waste treatment in textile industry in San Juan de Lurigancho. Materials and methods: It was considered a non-experimental, basic and descriptive study. The sample was composed of ten establishments in textile industry in San Juan de Lurigancho, selected by the use of the non-probability sampling. The waste treatment in textile industry was determined by using data gathering tools (Questionnaire) and data analysis by considering descriptive statistics. Results: It was evident that there is no an appropriate waste treatment process into the establishments, and it includes the lack of information about norms, in most of the establishments (70%); inappropriate strategies to identify the place where waste is produced, in most of the establishments (70%); inadequate manipulation in all of the establishments (100%) and ineffective waste final control, in most of the establishments (80%), once they are released from them. Conclusion: Waste treatment is not developed appropriately in the establishments because of the lack of control about procedures that are needed to reduce the negative effect of pollutants.